2014
DOI: 10.1371/journal.pone.0092648
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Trem2 Variant Associated with Triple Risk of Alzheimer’s Disease

Abstract: Alzheimer’s disease is one of the main causes of dementia among elderly individuals and leads to the neurodegeneration of different areas of the brain, resulting in memory impairments and loss of cognitive functions. Recently, a rare variant that is associated with 3-fold higher risk of Alzheimer’s disease onset has been found. The rare variant discovered is a missense mutation in the loop region of exon 2 of Trem2 (rs75932628-T, Arg47His). The aim of this study was to investigate the evidence for potential st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…The R47H variant is located within the extracellular immunoglobulin-like domain and recent results support a significant effect on ligand binding affinity as well as structural configuration of TREM2 [31], with possible subsequent signaling dysregulation. Here we demonstrate that the R47H variant is associated with distinct signaling in cases with AD.…”
Section: Discussionmentioning
confidence: 97%
“…The R47H variant is located within the extracellular immunoglobulin-like domain and recent results support a significant effect on ligand binding affinity as well as structural configuration of TREM2 [31], with possible subsequent signaling dysregulation. Here we demonstrate that the R47H variant is associated with distinct signaling in cases with AD.…”
Section: Discussionmentioning
confidence: 97%
“…Microglia depletion/inhibition in animal models of AD ameliorates memory loss in adult mice (Asai et al, ). In addition, Genomic wide association studies (GWAS) have identified variants of several immune genes are risk factors for late‐onset AD including CD33 and TREM2 (Abduljaleel et al, ; Hollingworth et al, ; Jonsson et al, ; Naj et al, ; Painter et al, ; Wang et al, ). A most recent three‐stage case‐controlled study of 85,133 subjects identified three new genome‐wide significant nonsynonymous variants in PLCG2, ABI3, TREM2 (Sims et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified a rare TREM2 rs75932628 variant (p.R47H) as a risk factor for AD, suggesting that the protein plays an important role in neurodegeneration [6,19,20]. Studies also identified the association with diseased risk for frontotemporal dementia (FTD) [16] and ALS [15].…”
Section: Discussionmentioning
confidence: 99%